An in-situ small angle x ray scattering analysis of nanopore formation during thermally induced chemical dealloying of brass thin foils - Bao Lin (Nature Portfolio, 2018)
Abstract The development of non-noble nano-porous metal materials is hindered by surface oxidation reactions and from the difficulty to generate long range order pore arrays. Dealloying is a promising route to generate such materials by selective chemical etching of metal alloy materials. This process can generate nano-metal materials with superior plasmonic, catalytic and adsorptive surface properties. Here, the impact of properties of the etching solution on the dealloying process to generate nano-pores across thin film alloys was investigated by in-situ SAXS dealloying experiments. Single phase CuZn alloys were used as model materials to evaluate the influence of the solution temperature on the pore formation kinetics. This novel analysis allowed to visualize the change in surface properties of the materials over time, including their surface area as well as their pore and ligament sizes. The dealloying kinetics at the very early stage of the process were found to be critical to both stable pore formation and stabilization. SAXS in-situ data were correlated to the morphological properties of the materials obtained from ex-situ samples by Rutherford back scattering and scanning electron microscopy.